Schistosomus reflexus in a Dog and a Cat - Bertolo, Paulo Henrique Leal; da Conceição, Maria Eduarda Bastos Andrade Moutinho; de Aguirra, Lucien Roberta Valente Miranda; Martins, Danielle Martinelli; de Macedo, Breno Costa; Coutinho, Leandro Nassar; Cardoso, Adriana Maciel de Castro; Pereira, Washington Luiz Assunção (Acta Scientiae Veterinariae, 2017)
Background: Schistosomus reflexus (SR) is a congenital anomaly, that the animal presents exposed abdominal and thoracic organs. The alterations includes limbs malformation, abnormal spinal column, liver and diaphragm hypoplasia, genitourinary and gastrointestinal changes, on this way, the fetus can not survive. The aim of this study was to report the first SR case in dog and cat in Brazil, and describe anatomical, pathological and radiographic changes. Case: The puppy had ventral midline defect in the abdominal and thoracic wall extending from the sternum to the pubis with viscera exposition, including the heart, lung, liver, stomach, intestine, spleen, kidneys, moreover right army was abnormal, however no spinal column was present. It was performed radiography to evaluate bone abnormalities, and was diagnosed agenesis of carpal, metacarpal and phalange bones. The kitten had ventral midline defect measuring 4 x 2 cm, in the abdominal wall and exposition of liver, stomach, intestine and spleen, as well as tibiotarsal joint arthrogryposis on both lags. It was performed fetus radiography and no spinal column change was diagnosed. Discussion: Schistosomus reflexus is a congenital abnormality common in ruminants. Although it was few reported in dogs and cats. The two cases in this study are the firsts reposts in Brazil in these especies. In our case, the dog had exposition of abdominal and thoracic organs and died one hour after born, similar to this, another author reported a case where the thoracic and abdominal evisceration and the puppy died ten minutes after born. However, in another case with abdominal evisceration only, the puppy survived for eight days. Probably it happened because respiratore function was not compromised. The kitten had abdominal opening only, in turn, other authors reported a case whose abdominal viscera exposition was by pelvic fissure, and another case, what presented thoracic and abdominal evisceration, like our dog case. Some authors affirm that this defect causes fetal dystocia on ruminants, because of the vertebral column abnormality, what promote passage difficult at born moment. On the other hand, dogs did not present these kind of changes and dystocia was not related to this pathology on cases in dogs and cats, however most of these authors performed cesarean because the female did not get normal born. As well as, on two cases in kitten were reported vertebral column abnormalities, what can be related to dystocia. Even no animal of our study present any vertebral column abnormality, other bone changes were found, like carpal, metacarpal and phalange agenesis on army of the dog and tibiotarsal joint arthrogryposis on both lags of the cat fetus. The others report in dogs did not found vertebral column or bone changes, but in cats it was observed vertebral column abnormalities and other changes, like arthrogryposis on four limbs, skull flattening, mandibular brachignathism, reduced ossification of the cranial vault bones, palatoschisis and unfused eyelids. SR etiology is not clearly known, it may be related with genetic, mechanic, endocrine, metabolic, nutrition and infectious factors. The moment of embryonic development, where these factors influence the changes is related with abnormality grade. Although, Chromosomic abnormalities, like chromatid and chromosome breaks, non-homologous pairing of chromosomes was shown. In this study the bitch did not present any metabolic, endocrine or nutritional change, on other hand the queen was submitted to exogenous hormonal treatment to avoid pregnancy, what may be related to SR development. SR is a rare abnormality in dog and cat, fetus radiographic, anatomical and pathological findings confirmed to being this congenital defect, and this are the first reports in Brazil in these species.